Plasmonic Imaging of Electrochemical Reactions at Individual Prussian Blue Nanoparticles - Garcia, Adaly; Wang, Kinsley; Bedier, Fatima; Benavides, Miriam; Wan, Zijian; Wang, Shaopeng; Wang, Yixian (Frontiers in Chemistry, 2021)
Prussian blue is an iron-cyanide-based pigment steadily becoming a widely used electrochemical sensor in detecting hydrogen peroxide at low concentration levels. Prussian blue nanoparticles (PBNPs) have been extensively studied using traditional ensemble methods, which only provide averaged information. Investigating PBNPs at a single entity level is paramount for correlating the electrochemical activities to particle structures and will shed light on the major factors governing the catalyst activity of these nanoparticles. Here we report on using plasmonic electrochemical microscopy (PEM) to study the electrochemistry of PBNPs at the individual nanoparticle level. First, two types of PBNPs were synthesized; type I synthesized with double precursors method and type II synthesized with polyvinylpyrrolidone (PVP) assisted single precursor method. Second, both PBNPs types were compared on their electrochemical reduction to form Prussian white, and the effect from the different particle structures was investigated. Type I PBNPs provided better PEM sensitivity and were used to study the catalytic reduction of hydrogen peroxide. Progressively decreasing plasmonic signals with respect to increasing hydrogen peroxide concentration were observed, which demonstrated the capability of sensing hydrogen peroxide at single nanoparticle level utilizing this optical imaging technique.